Analytic model for tangential YORP - Golubov, Oleksiy (arXiv.org, 2017)
The tangential YORP effect (TYORP) plays a significant role in the dynamical evolution of asteroids, and up to now has only been studied numerically. This paper describes the first analytic model of the TYORP effect. Although the model rests on numerous physical and mathematical simplifications, the final analytic expression for TYORP is found to be in agreement with the results of rigorous numeric simulations to the accuracy of several tens per cent. The obtained analytic expression is used to estimate the TYORP produced by the non-flat surface of regolith, -- a contribution to TYORP that has never been considered. It is found that the contribution to TYORP arising from regolith can be comparable to the conventional TYORP produced by boulders. Then, the analytic expression is fitted with a log-normal function and used to integrate TYORP over all boulder sizes. The general trend of TYORP for multiple boulders appears qualitatively similar to the trend of one boulder, and also demonstrates a maximal TYORP at some particular rotation rate. The obtained expression for integrated TYORP may be instrumental for simulations of evolution of asteroids subject to TYORP. To conclude, the physical origin of TYORP is discussed in light of the constructed analytic model.